Power Of Friendship Between King George ViAnd Lionel Logue In The King Speech Movie (2010) Directed By Tom Hooper: An Individual Psychological Approach - Aina, Corry, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2014)
The major issue of this study is; to know the power of best friends between King George VI and Lionel Logue in The King's Speech? The objective of this study is to analyze the structural elements of the movie The King's Speech and analyzing The King's Speech movie based on the psychological approach. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data source is The King's Speech movie directed by Tom Hooper and script movie written by David Seidler. The secondary data sources are the data that support the analysis. The data analysis method is descriptive qualitative analysis based on individual psychological approach. The results of the study show; the structural analysis of The King's George IV and Lionel Logue is connected to each other. The setting of this movie is in Wembley and Buckingham Palace. The director showed the trust appears in every people without seeing gender and status. Based on individual psychological approach, the striving for superiority of the king and Lionel appears where the power of the king to become a good father, he tries to get involved in every activity in the house, especially when he tries to tell the story for his daughters. The inferiority feeling on this movie appears starts from the King George, where at the first time he must do the speech in front of the people of England. The fictional finalism of Lionel who wants to become an artist. The fictional finalism of King George where he is the grope king who really wants to recover. The creative power of Lionel to help the king appears related with the simple sentence 'I am a thistle sifter. I have a sieve of sifted thistles and a sieve of unsifted thistles'. The style of life of the movie is the social useful types belong to Lionel and ruling type belongs to the King. The social useful types be seen on every Lionel activity on helping people to recover from the speech sickness.